Herbal Shampoo Tablet: Benefits, Preparation and Evaluation - Reddy, V. Sarovar (Asian Journal of Pharmaceutics (AJP), 2025)
Aim: In the contemporary era, there is a growing preference for natural and herbal alternatives due to their renewability, minimal adverse effects, and cost-effectiveness. This novel work aims to prepare and evaluate an environmentally conscious herbal shampoo in tablet form. This pioneering endeavor by the formulator seeks to create an essential cosmetic product for hair hygiene and attractiveness using natural ingredients. Material and Methods: Two formulations, F1 and F2, were developed with varying concentrations of ingredients to incorporate desired properties such as cosmetic enhancement, hair conditioning, stimulation, antimicrobial action, and hair growth promotion. The shampoo tablets were prepared using the direct compression method and subjected to a battery of tests, including particle size analysis, flow property assessment (angle of repose, bulk density, tapped density, Hausner ratio, Carr’s index), and physicochemical evaluation (hardness, pH determination, loss on drying, swelling index, wetting time, dirt dispersion, foaming ability, and foam stability). Results: The conditioning performance evaluation aimed to ensure that the shampoo tablets maintain environmental sustainability by posing no harm to soil or atmosphere after use. Conclusion: Both formulations exhibit promising characteristics for further investigation.